2014
DOI: 10.4172/2161-0509-4.1000141
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Metabolic Syndrome in a Burkina Faso Urban Area: Prevalence,Associated Factors and Comorbidities

Abstract: Background: The prevalence of obesity and metabolic syndrome is not just a problem of the developed countries but is also with a growing trend in developing countries, especially in urban areas. We aimed to estimate the prevalence of obesity and metabolic syndrome in the urban population living in Ouagadougou, Burkina Faso, and to investigate the factors and comorbidities associated with them. Methods: Data were collected in two rounds (in March and December 2011) from two different neighbourhoods (peripheral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 13 publications
0
7
1
Order By: Relevance
“…This association was direct in men as shown in the SEM, but negative and indirect (acting through lifestyle and sociodemographic factors) in women (Figures 1 & 2). These results differ from Sagna and collaborators who concluded in their study in peripheral and central urban areas in Burkina Faso that increased obesity was associated with older age [22]. …”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This association was direct in men as shown in the SEM, but negative and indirect (acting through lifestyle and sociodemographic factors) in women (Figures 1 & 2). These results differ from Sagna and collaborators who concluded in their study in peripheral and central urban areas in Burkina Faso that increased obesity was associated with older age [22]. …”
Section: Discussioncontrasting
confidence: 99%
“…In the STEPwise approach to Surveillance (STEPS), national survey for non-communicable diseases, it was reported that women were more overweight and obese than men [17]. Other studies in urban Burkina Faso or hospital (outpatients) settings reported that women were more overweight and obese than men [12,2225]. In their study in four sub-Saharan countries (Nigeria, South Africa, Tanzania, Uganda) Ajayi et al also reported the gender difference in favour of women [11].…”
Section: Discussionmentioning
confidence: 99%
“…According to a survey in 2008, it has been noticed that over 1 billion of people are suffering with obesity and are not taking care of their body as well [7].…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence of obesity reported in Ouagadougou, Burkina Faso in 2014, gave a 30.5%, 22% prevalence of overweight and obesity respectively [23]. Systemic reviews and other studies on the subject suggest high and wide ranges in the prevalence of overweight and obesity [5]…”
Section: Introductionmentioning
confidence: 99%